MENURUNKAN POTENSI RESIKO KECELAKAAN KERJA MENGGUNAKAN METODE SWIFT (THE STRUCTURED WHAT IF TECHNIQUE) DI LINI PROSES FORGING - erwin barita tambunan; Fitri Sulastri; Pendi Rusman (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2022)
Analysis of Occupational Health and Safety Risks in Forging Forging Lines Using the SWIFT (The Structured What If) Method At PT. XYZ. PT. XYZ is a manufacturing company engaged in the production of household appliances such as spoons, forks and knives. During the second quarter of 2021, the number of work accident cases that occurred was 10 cases. For this reason, it is necessary to conduct research that aims to minimize the risk of hazards that occur in the forging line using the SWIFT method. The results of the study contained 13 potential hazards with a classification based on the RRN value of 2 including low priority categories, 6 medium priority categories, 5 risks in the main priority categories. The improvement recommendations given can reduce the risk of work accidents from the previous 13 risks of work accidents with categories of 2 mild risk, 6 moderate risk, and 5 severe risk, now to 2 mild risk, 11 moderate risk and 0 severe risk.